The Participation Of The Student’s Parents Association In Increasing Students Learning Motivation In Islamic Religious Education Lesson At Sdit As Syafi'iyah Ponorogo Indonesia - et. al., Rofiatul Hosna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Islamic educational institutions have their own challenges in achieving their vision and mission. The parents' association of pupils has an important role in developing education in schools.This study aims to find out the participation of student’s parents association in increasing student motivation towards Islamic religious education lesson in SDIT As Syafiiyah Ponorogo. This research uses a qualitative approach which are parents, teachers, and students as subjects. The techniques of collecting data used interviews, documentation and observation. Data analysis of this research used data collection, data reduction, data presentation, and conclusions. Examination of data using triangulation of research results shows that the participation of parents' parents in increasing motivation to learn in Islamic religious education at SDIT As Syafiiyah Ponorogo with: as a decision maker, as an implementer, as a beneficiary, as an evaluator. Factors supporting the participation of student’s parents association in increasing learning motivation in Islamic religious education lessons are transparant school management, excellent service, good coordination between schools / teachers and parents, good programs, well educated parents, good teacher HR. The inhibiting factors are the lack of students and students’ parents level of awareness of Islamic religious education lessons, Lack of coordination between student parents and teachers / schools, unclear programs of school,and busy parents.